Influence of door handles design in effort perception: accessibility and usability - Paschoarelli, Luis Carlos [UNESP]; Santos, Raquel; Bruno, Paula (IOS Press, 2012)
The application of ergonomics in product design is essential to its accessibility and usability. The development of manual devices should be based on ergonomic principles. Effort perception analysis is an essential approach to understand the physical and subjective aspects of the interface. The objective of the present study was to analyze the effort perception during a simulated task with different door handles by Portuguese subjects of both genders and different ages. This transversal study agreed with ethical aspects. 180 subjects of both genders pertaining to three age groups have participated. Five door handles with different shapes were evaluated. A subjective numeric rating scale of 5 levels was used to evaluate the effort. For statistical analysis it was applied the Friedman non-parametric test. The results have showed no significant differences of effort perception in door handles "A" and "B"; "A" and "D"; and "D" and "C". Door handle "E" presented the lowest values of all. In general, there's an inverse relationship between the results of biomechanical studies and the effort perception of the same task activity. This shows that door handles design influence directly these two variables and can interfere in the accessibility and usability of these kinds of products.
Keywords: ergonomic design; accessibility; usability; door handles